Enrichment Book Design Based on Laboratory Results for Viruses on Plants Material - Siti Rodhiah Azhari; Suranto Suranto; Muzzazinah Muzzazinah (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to determine the design of the development of an enrichment book based on laboratory results of infection in plants. The subtopics presented are infection in plants and detection of infected plants by using isozymes. The initial stage that is carried out is that researchers conduct research in the field and in the laboratory to obtain information in writing the manuscript or the content of the material to be presented in the enrichment book. The development of the enrichment book refers to the book development procedure by Sitepu (2012), are script writing, illustration, editing, cover design, and printing. The design for the development of the enrichment book is arranged in several parts, are the cover page, the initial page, the content section, the evaluation page, and the final page. The development of the enrichment book will be tested on high school students who have obtained infection material on plants. The development of this enrichment book is based on the lack of utilization of research results as teaching materials in schools. Therefore, this biological enrichment book was developed based on the results of research conducted, namely disease incidence (di), disease severity (ds), and isozyme characterization of virus-infected chili plants. The development of this enrichment book is expected to increase students' insight, knowledge, and curiosity and be used as a learning resource to understand the concept of plant infection material widely.